2006
DOI: 10.1093/ajcn/84.4.871
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index and glycemic load in relation to changes in body weight, body fat distribution, and body composition in adult Danes

Abstract: High-GI diets may lead to increases in BW, body fat mass, and WC in women, especially in sedentary women, which suggests that physical activity may protect against diet-induced weight gain. No associations with GI were observed in men, which suggests sex differences in the association between GI and obesity development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 44 publications
3
58
3
1
Order By: Relevance
“…In our current study, a 10-unit GI difference was associated with a waist circumference change of 0.19 cm per year or 0.26 cm per year, depending on the adjustment strategies applied. Although weaker when compared with earlier observations, 16 this association was independent of weight change because GI was not in an overall association with weight change. Increase in waist circumference independent of weight change indicates an accumulation of visceral fat, which has been found to be strongly associated with insulin resistance, and thus the risk of type 2 diabetes and CVDs.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…In our current study, a 10-unit GI difference was associated with a waist circumference change of 0.19 cm per year or 0.26 cm per year, depending on the adjustment strategies applied. Although weaker when compared with earlier observations, 16 this association was independent of weight change because GI was not in an overall association with weight change. Increase in waist circumference independent of weight change indicates an accumulation of visceral fat, which has been found to be strongly associated with insulin resistance, and thus the risk of type 2 diabetes and CVDs.…”
Section: Discussioncontrasting
confidence: 95%
“…[9][10][11] Few long-term cohort studies among free-living populations have been conducted to explore associations between GI or GL and weight change. 15,16 In these two cohort studies, a positive association between GI, but not GL, and weight change has been observed, at least in subgroups. 16 Compared with our study, these studies were much smaller in sample size, were conducted among a more homogeneous population and had measured weight data.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations